The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1109/lwc.2014.2342736
|View full text |Cite
|
Sign up to set email alerts
|

Optimal LAP Altitude for Maximum Coverage

Abstract: Low-altitude aerial platforms (LAPs) have recently gained significant popularity as key enablers for rapid deployable relief networks where coverage is provided by onboard radio heads. These platforms are capable of delivering essential wireless communication for public safety agencies in remote areas or during the aftermath of natural disasters. In this letter, we present an analytical approach to optimizing the altitude of such platforms to provide maximum radio coverage on the ground. Our analysis shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
1,950
1
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,415 publications
(1,966 citation statements)
references
References 5 publications
6
1,950
1
9
Order By: Relevance
“…Simulation results demonstrated that the impact of elevation angle was significant on the excess path loss. In [10], the closed-form expression was formulated for determining the coverage performance in terms of the maximum cell radius and the optimal altitude. In this study, the free space path loss model was extended using the excessive attenuation factor for different LOS and NLOS propagation conditions.…”
Section: A Deterministicmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results demonstrated that the impact of elevation angle was significant on the excess path loss. In [10], the closed-form expression was formulated for determining the coverage performance in terms of the maximum cell radius and the optimal altitude. In this study, the free space path loss model was extended using the excessive attenuation factor for different LOS and NLOS propagation conditions.…”
Section: A Deterministicmentioning
confidence: 99%
“…Such models are useful for studying large-scale fading effects in the channel [6], [7]. Hence the propagation conditions [8], [9] can provide coverage analysis and indicate the optimal UAV position [10]- [12]. The second approach is to develop a tapped delay line (TDL) model to characterize the direct path as well as the multipath components.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation channel is modeled by probabilistic LoS, in which the probability of having a LoS connection between a user and the drone is as follows [9] …”
Section: System Modelmentioning
confidence: 99%
“…The study does not explore cross-tier interference management in the presence of large scale DSCN deployment. The authors in [8], based on the results of [9], present a 3D optimization problem for DSCs with the aim to maximize the number of users to be covered by such DSCs using a numerical search algorithm to satisfy the defined quality of service (QoS) measures. The paper focuses on drone empowered future cellular networks for disaster recovery/ public safety.…”
Section: B Related Workmentioning
confidence: 99%